Surgical management of anal stenosis: anoplasty with or without sphincterotomy - Mehdi Tahamtan; Leila Ghahramani; Hajar Khazraei; Yaser Tolouei Tabar; Alimohammad Bananzadeh; Seyed Vahid Hosseini; Ahmad Izadpanah; Fahime Hajihosseini (Journal of Coloproctology, 2017)
Aim: Anal stenosis is an uncommon complication of anorectal surgery, mostly resulting from circumferential hemorrhoidectomy or resection of the skin tag in surgical management of chronic anal fissure. The aim of anoplasty is to restore normal function to the anus by dividing the stricture and widening the anal canal. Internal sphincterotomy may cause gas incontinence and if we manage the stenosis without sphincterotomy it could be failed. Could we use anoplasty without sphincterotomy? Method: The patients with anal stenosis were assigned in to two groups. The first group underwent Y-V anoplasty without partial lateral internal sphinctrotomy and the second one underwent Y-V anoplasty with partial lateral internal sphinctrotomy. Result: A total of 25 patients (10 male and 15 female) underwent anoplasty, 14 without partial lateral internal sphincterotomy and 11 patients with partial lateral internal sphincterotomy. The healing rate of stenosis was 91% and 93% in groups undergoing anoplasty without partial lateral internal sphinctrotomy and anoplasty with partial lateral internal sphictrotomy, respectively (p value 0.69). There was no significant change in both groups for post-operative incontinence complaints. Conclusion: The healing rate of anal stenosis was the same in the patients who underwent Y-V anoplasty with or without partial lateral internal sphinctrotomy. There was no significant change in post-operation incontinence between the two groups. Therefore, Y-V anoplasty would be a safe and simple surgical method in selected patients. Partial lateral internal sphinctrotomy procedure has been noticed in individual cases. Resumo: Objetivo: A estenose anal é complicação incomum da cirurgia anorretal, sendo principalmente resultante de uma hemorroidectomia circunferencial ou ressecção do pólipo cutâneo no tratamento cirúrgico da fissura anal crônica. O objetivo da anoplastia é a restauração da função normal do ânus, mediante a divisão da constrição e alargamento do canal anal. A esfincterotomia interna pode causar incontinência gasosa; e se tratarmos a estenose sem esfincterotomia, poderá ocorrer insucesso. Poderíamos usar a anoplastia sem esfincterotomia? Método: Os pacientes com estenose anal foram designados para dois grupos. O primeiro grupo foi tratado com anoplastia em Y-V sem esfincterotomia interna lateral parcial, e o segundo grupo foi tratado com anoplastia em Y-V com esfincterotomia interna lateral parcial. Resultado: No total, 25 pacientes (10 homens e 15 mulheres) foram tratados com anoplastia–14 sem esfincterotomia interna lateral parcial, e 11 com esfincterotomia interna lateral parcial. Os percentuais de cura da estenose foram de 91% e 93% nos grupos tratados com anoplastia sem esfincterotomia interna lateral parcial e com esfincterotomia interna lateral parcial, respectivamente (p = 0,69). Não ocorreu mudança significativa nos dois grupos com relação às queixas de incontinência pós-operatória. Conclusão: O percentual de cura da estenose anal foi igual nos pacientes tratados com anoplastia em Y-V com ou sem esfincterotomia interna lateral parcial. Não foi observada mudança significativa na incontinência pós-operatória entre os dois grupos. Portanto, a anoplastia em Y-V seria um método cirúrgico seguro e simples em pacientes selecionados. Em casos isolados, o procedimento de esfincterotomia interna lateral parcial tem sido observado. Keywords: Anoplasty, Sphinctrotomy, Anal stenosis, Palavras-chave: Anoplastia, Esfincteroplastia, Estenose anal